Knowledge, attitudes and practices on water, sanitation and hygiene among residents in selected barangays of the Maguindanao del Norte and del Sur - Kadtong, Maeda Langguyuan; Unos, Musa A.; Unos, Ansare K.; Abdul, Badrudin K.; Omar, Abdulnasser T. (Edelweiss Applied Science and Technology, 2025)
This study examined the knowledge, attitudes, and practices related to water, sanitation, and hygiene (WASH) among residents in selected barangays of Maguindanao. It specifically explored sources of household water for domestic and drinking purposes, water treatment practices, toilet facilities, awareness of open defecation, waste disposal methods, and hygiene practices such as handwashing and tooth brushing. Using a descriptive research design, data were gathered from 60 household members across six barangays in Maguindanao del Sur and Maguindanao del Norte through purposive sampling. Findings revealed that most households (55%) obtained drinking water from piped yard/plot sources, while 31.66% used improvised filters such as cloth or sponge to make water safer for consumption. A significant number of households (63.33%) lacked toilet facilities, leading to open defecation in bushes, fields, or rivers, although most respondents demonstrated awareness of its negative health effects. In terms of waste management, 36.66% practiced direct disposal without storage, and 61.66% discarded garbage near their homes. The majority of household waste consisted of paper (83.33%), with 78.33% of households lacking trash bins. Hygiene practices were also found to be inadequate, with respondents primarily washing hands in kitchen-built lavatories but brushing their teeth rarely, as reflected in a low mean score of 1.661. In conclusion, while residents showed awareness of sanitation-related health risks, gaps remained in toilet availability, water treatment, waste management, and personal hygiene practices. These findings highlight the urgent need for improved facilities, community education, and strengthened WASH interventions in the studied barangays.